2017
DOI: 10.1038/s41598-017-00570-5
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol S negatively affects the meotic maturation of pig oocytes

Abstract: Bisphenol A (BPA), a chemical component of plastics, is a widely distributed environmental pollutant and contaminant of water, air, and food that negatively impacts human health. Concerns regarding BPA have led to the use of BPA-free alternatives, one of which is bisphenol S (BPS). However, the effects of BPS are not well characterized, and its specific effects on reproduction and fertility remain unknown. It is therefore necessary to evaluate any effects of BPS on mammalian oocytes. The present study is the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 62 publications
5
40
0
Order By: Relevance
“…For example, oestradiol caused reductions in oocyte maturation and increased spindle abnormalities (Beker, Colenbrander, & Bevers, ; Woudenberg, Tol, Roelen, Colenbrander, & Bevers, ) but also enhanced oocyte cytoplasmic maturation and improved fertilization and cleavage rates (Tesarik & Mendoza, ). A recent study demonstrated that BPS induced abnormalities in porcine oocytes, including in vitro maturation rates, spindle morphology and cumulus expansion (Žalmanová et al., ). Investigation into the effects of BPS in the whole follicle is necessary to elucidate the modulating impact that intrafollicular interactions between cell types may have.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, oestradiol caused reductions in oocyte maturation and increased spindle abnormalities (Beker, Colenbrander, & Bevers, ; Woudenberg, Tol, Roelen, Colenbrander, & Bevers, ) but also enhanced oocyte cytoplasmic maturation and improved fertilization and cleavage rates (Tesarik & Mendoza, ). A recent study demonstrated that BPS induced abnormalities in porcine oocytes, including in vitro maturation rates, spindle morphology and cumulus expansion (Žalmanová et al., ). Investigation into the effects of BPS in the whole follicle is necessary to elucidate the modulating impact that intrafollicular interactions between cell types may have.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that BPS increased oestradiol production by bovine granulosa cells is consistent with previous reports in the zebrafish and mice where BPS upregulated plasma oestradiol levels (Ji et al., ; Naderi et al., ; Shi, Sekulovski, MacLean, & Hayashi, ). Although beyond the scope of this study, further investigation will reveal whether BPS alters oestradiol production by affecting aromatase expression, such as in porcine cumulus cells and oocytes (Žalmanová et al., ), or via an alternate mechanism, such as changes in the aromatase inhibitor PPARγ, as is the case in murine pre‐adipocytes (Ahmed & Atlas, ). In addition to altering aromatase expression in porcine cumulus cells and oocytes, BPS also altered oestrogen receptor α and β expression (Žalmanová et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In porcine, BPS affected meiotic division of the oocytes and the expression and distribution of ERβ, ERα and aromatase. 62 BPS reduced egg production and the gonadosomatic index (gonad weight/ body weight) in zebrafish. 63 BPS and BPF increased the uterine weight in rats, 64 but another study did not find the same effect.…”
Section: Other Bisphenols and Female Reproductive Functionsmentioning
confidence: 99%